Gleason pattern 5 is associated with an increased risk for metastasis following androgen deprivation therapy and radiation: An analysis of RTOG 9202 and 9902. (December 2019) - Hamstra, Daniel A.; Pugh, Stephanie L.; Lepor, Herbert; Rosenthal, Seth A.; Pienta, Kenneth J.; Gomella, Leonard; Peters, Christopher; D'Souza, David Paul; Zeitzer, Kenneth L.; Jones, Christopher U.; Hall, William A.; Horwitz, Eric; et al.
Highlights: Gleason pattern 5 increased the risk of distant metastases compared to Gleason 8 (4 + 4). This may impact treatment decisions and risk stratification. Gleason 8–10 should not be utilized as a homogenous group given differences based upon GP5. Abstract: Background/purpose: Stratification of Gleason score (GS) into three categories (2–6, 7, and 8–10) may not fully utilize its prognostic discrimination, with Gleason pattern 5 (GP5) previously identified as an independent adverse factor. Materials/methods: Patients treated on RTOG 9202 ( n = 1292) or RTOG 9902 ( n = 378) were pooled and assessed for association of GS and GP5 on biochemical failure (BF), local failure (LF), distant metastasis (DM), and overall survival (OS). Fine and Gray's regression and cumulative incidence methods were used for univariate and multivariate analyses. Results: With median follow-up of 9.4 years, patients with GS 8–10 with GP5 had worse outcome than GS 4 + 4 for DM on both RTOG9202 ( p = 0.038) and RTOG9902 ( p < 0.001) with a trend toward worse OS ( p = 0.059 and p = 0.089, respectively), but without differences in BF or LF. At 10-years DM was higher by 11% (RTOG 9202) and 18% (RTOG 9902) with GP5 compared to GS 4 + 4. On multivariate analysis restricted to long-term androgen deprivation therapy the presence of GP5 substantially increased distant metastasis (HR = 0.43, 95%CI: 0.24–0.76, p = 0.0039) with a trend toward worse OS (HR:0.74, 95% CI:0.54–1.0, p = 0.052) without association with LF (HR:0.55, 95%CI:0.28–1.09, p = 0.085) or BF (HR:1.15, 95%CI:0.84–1.59, p = 0.39). We did not observed substantial differences between Gleason 3 + 5, 5 + 3, or Gleason 9–10. Conclusions: These results validate GP5 as an independent prognostic factor which is strongest for DM. As a result GP5 should be considered when stratifying patients with GS 8 and may be a patient population in which to evaluate newly approved systemic therapies or additional local treatments.